The dynamics of the Egyptian social contract: How the political changes affected the poor. (February 2021) - Ibrahim, Solava
Highlights: Political uprisings in Egypt left the poor in deprived communities worse off. The new social contract exchanges political and socio-economic rights for political stability. The same unfulfilled aspirations and problems in education and employment persisted over time. The uprisings led to a more repressive state, a highly polarised society and growth did not trickle down to the poor. Economic crises affected the poor, esp. women and youth in urban areas. Abstract: How have the uprisings in 2011 and 2013 affected deprived communities in Egypt? Adopting a social contract approach, this longitudinal study tracks the same individuals in Manshiet Nasser and Menia over a ten-year period (2006–2015) articulating their wellbeing priorities, unfulfilled aspirations, problems and perceptions on the social contract over time. This grounded micro-level study argues that the uprisings; which were meant to end the old social contract that traded off political rights with socio-economic benefits; have in fact post-2013 led to a new bargain that forgoes both sets of rights in exchange for political stability. The analysis shows the persistence of the same wellbeing priorities, problems and unfulfilled aspirations, esp. in employment, income generation, housing and education. This indicates the repeated failure of the state to enact a new social contract that addresses these needs. The burden of the post-revolutionary economic crises fell mainly on the poor, especially female headed households in urban areas and young informal workers – both suffering from high inflation and unemployment. Paradoxically, whilst the January 2011 uprising called for a new social contract promoting 'bread, freedom and social justice', it led post-2013 to a more exclusionary one. Blaming the uprisings for the political turmoil and economic crises, deprived communities were therefore willing to accept a new social contract that not only denies their basic political rights but also undermines the socio-economic benefits - guaranteed under the old populist social contract. They thus tolerated the state's failure to fulfil these socio-economic rights in exchange for political stability. The sustainability of the current social contract however remains questionable. Politically, the uprisings had a contradictory effect as they raised political awareness; but undermined feelings of citizenship and led to radicalisation when the democratic transition failed. The new social contract thus not only failed to address the 'revolution of rising expectations' after the uprisings, but also jeopardizes long-term political stability in Egypt. Forging a sustainable more inclusive social contract thus remains a major challenge the current regime needs to address.